Einstein connections on Lorentzian spheres - Draper-Fontanals, Cristina (My University, 2020)
A comparison between Riemannian and Lorentzian spheres as regards the existence of Einstein connections with skew-torsion
Keywords: Lorenz, Ecuaciones de; Geometría; Invariant connection; Berger sphere; Einstein connection; Lorentz metric